2021
DOI: 10.1111/and.14003
|View full text |Cite
|
Sign up to set email alerts
|

Serum folic acid levels and erectile dysfunction: A meta‐analysis and systematic review

Abstract: The aim of this study was to assess the relationship between serum folic acid (FA) levels and erectile dysfunction (ED) through a meta‐analysis. A research was conducted in MEDLINE via PubMed, Cochrane Library, EMBASE and Web of Science up to 22 November 2020 to identify studies related to FA and ED. Two authors independently screened the literature, evaluated methodological quality and extracted the data. We used RevMan5.3 and STATA 14.0 for meta‐analysis. A total of six studies including 1,842 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In addition, our study found that differences in FA, vitamin B12 and HCY between groups seemed to be more pronounced in the younger participants (age < 35 yr). Our previous meta‐analysis first proposed that there was such a trend in FA differences between ED patients and the control group, which was well verified in this study (Xu et al., 2021). This may be due to the prevalence of FA and vitamin B12 deficiency among older people, a confounding factor that masks differences between the groups (Mooijaart et al., 2005).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, our study found that differences in FA, vitamin B12 and HCY between groups seemed to be more pronounced in the younger participants (age < 35 yr). Our previous meta‐analysis first proposed that there was such a trend in FA differences between ED patients and the control group, which was well verified in this study (Xu et al., 2021). This may be due to the prevalence of FA and vitamin B12 deficiency among older people, a confounding factor that masks differences between the groups (Mooijaart et al., 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Yan et al(Yan et al., 2014) first found that the serum folate level of ED patients was lower than that of healthy controls. Subsequent studies and our latest meta‐analysis also verified this difference (Attia et al., 2019; Karabakan et al., 2016; Sansone et al., 2018; Xu et al., 2021). Previous studies have explained the link between low FA levels and ED from the perspective of HCY metabolism, but in fact, only two studies have measured HCY and FA levels at the same time.…”
Section: Introductionmentioning
confidence: 63%
“…6 In several studies and meta-analyses after Yan et al revealed this correlation, ED patients were shown to have low FA levels. [18][19][20][21] However, only a few studies examined the correlation of vit B12, an important cofactor in HS metabolism, with FA, HS levels, and ED. The first of these studies identified a weak correlation, while a later study revealed a negative correlation between vit B12 levels and HS levels and a correlation between vit B12 deficiency and ED.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, ED in diabetic patients treated with the combination of tadalafil and folic acid 5 mg improved significantly as compared with the placebo group [111]. The degree of folic acid deficiency may reflect the severity of ED [112]. It appears to be more commonly seen in younger individuals [112].…”
Section: Vitamins/micronutrientsmentioning
confidence: 96%
“…The degree of folic acid deficiency may reflect the severity of ED [112]. It appears to be more commonly seen in younger individuals [112]. This association may be mediated by homocysteine and higher than usual doses of folic acid may be necessary to normalize serum homocysteine levels [113].…”
Section: Vitamins/micronutrientsmentioning
confidence: 99%